Observations of cattle use of prairie dog towns - Guenther, Debra A., author; Detling, James K., author; American Society for Range Management, publisher (Colorado State University. Libraries, 2003)
We investigated the use of prairie dog towns by cattle (Bos taurus) on the shortgrass steppe of northeastern Colorado by conducting surveys of cattle and vegetation from June to August 1999. Cattle presence and behavior were recorded 3 times a week during driving surveys of 15 black-tailed prairie dog (Cynomys ludovicianus) towns. A subset of 3 pastures with prairie dog towns was intensively surveyed twice weekly wherein the habitat and activity of a randomly chosen focal animal was recorded every 6 minutes for 3.5 hours. Bite and step counts of other individuals were recorded for 5-minute intervals. Vegetation height and cover data were collected monthly on each of 6 habitats. Results from driving surveys and intensively surveyed pastures were similar; cattle neither significantly preferred nor avoided prairie dog towns. Bare ground cover on prairie dog towns did not significantly differ from most other habitats, but vegetation on prairie dog towns was significantly shorter on (mean = 6.7 cm) than that off (mean = 11.9 cm) prairie dog towns. Nevertheless, foraging observations indicated that there was no significant difference between cattle foraging rates on swales (70.9 bites/min) and prairie dog towns (69.5 bites/min). Thus, cattle on the shortgrass steppe appear to use prairie dog towns in proportion to their availability and, while there, they graze as intensively as they do on habitats not inhabited by prairie dogs.
Abstract in English and Spanish.
Keywords: grazing; shortgrass steppe; cattle; prairie dogs; Cynomys ludovicianus